Metformin-induced lactic acidosis with emphasis on the anion gap - Blough, Britton (Proc (Bayl Univ Med Cent), 2015)
The presence of an anion gap in a diabetic patient, especially if associated with evidence of compromised renal function, should prompt clinicians to consider metformin as a contributing factor. This consideration is especially important in patients with severe anion gaps associated with lactic acidosis out of proportion to the patient's clinical presentation.